A qualitative approach to mobile robot navigation using RFID - Hossain, Mahbuba; Rashid, Muhammad Mahbubur; Bhuiyan, Moinul; Ahmed, Sayem; Akhtaruzzaman, Md. (IOP Publishing, 2013)
Radio Frequency Identification (RFID) system allows automatic identification of items with RFID tags using radio-waves. As the RFID tag has its unique identification number, it is also possible to detect a specific region where the RFID tag lies in. Recently it is widely been used in mobile robot navigation, localization, and mapping both in indoor and outdoor environment. This paper represents a navigation strategy for autonomous mobile robot using passive RFID system. Conventional approaches, such as landmark or dead-reckoning with excessive number of sensors, have complexities in establishing the navigation and localization process. The proposed method satisfies less complexity in navigation strategy as well as estimation of not only the position but also the orientation of the autonomous robot. In this research, polar coordinate system is adopted on the navigation surface where RFID tags are places in a grid with constant displacements. This paper also presents the performance comparisons among various grid architectures through simulation to establish a better solution of the navigation system. In addition, some stationary obstacles are introduced in the navigation environment to satisfy the viability of the navigation process of the autonomous mobile robot.